A search for prompt lepton-jets in pp collisions at √s = 8 TeV with the ATLAS detector - Aad, Georges; Anders, Christoph; Andrei, George Victor; Baas, Alessandra Edda; Brandt, Oleg; Davygora, Yuriy; Djuvsland, Julia Isabell; Dunford, Monica; Geisler, Manuel Patrice; Giulini, Maddalena; Hanke, Paul; Jongmanns, Jan; et al. (Journal of high energy physics, 2016)
A search is presented for a new, light boson with a mass of about 1 GeV and decaying promptly to jets of collimated electrons and/or muons (lepton-jets). The analysis is performed with 20.3 fb−1 of data collected by the ATLAS detector at the Large Hadron Collider in proton-proton collisions at a centre-of-mass energy of 8 TeV. Events are required to contain at least two lepton-jets. This study finds no statistically significant deviation from predictions of the Standard Model and places 95% confidence-level upper limits on the contribution of new phenomena beyond the SM, incuding SUSY-portal and Higgs-portal models, on the number of events with lepton-jets.
*The ATLAS collaboration: G. Aad, C.F. Anders, V. Andrei, A.E. Baas, O. Brandt, Y. Davygora, J.I. Djuvsland, M. Dunford, M.P. Geisler, M. Giulini, P. Hanke. J. Jongmanns, E.-E. Kluge, M. Kolb, M. Kretz, A. Kugel, V.S. Lang, M. Lisovyi, K. Meier, H. Meyer zu Theenhausen, D.I. Narrias Villar, M. Sahinsoy, S. Schaetzel, V. Scharf, S. Schmitt, A. Schoening, H.-C. Schultz-Coulon, D. Sosa, R. Stamen, P. Starovoitov, S. Suchek, M. Wessels [und sehr viele weitere Personen]
Im Titel steht der Buchstabe s unter dem Wurzelsymbol
Gesehen am 30.06.2020